Organization of bibliographical materials through a data base-catalogue- at the reading room, bachelor in basic education with a major in english as a foreign language, Distrital University (2009)
The reading room is a facility that the project LEBEI has to support the processes of English language teaching and learning, so the students of this program can take advantage of the materials that are there. In order to access to this material it is necessary to have a catalogue to identify the location of the specific material that is needed. This project pointed to the process of creating an electronic data base -catalogue in order to organize the bibliographical materials in the reading room, which would make easier for users the access to the materials. Furthermore, this project attempted to promote autonomous learning, since the creation of such a data base would allow students or users to consult the materials at the reading room in a more efficient way, and thus take advantage of their time reading or researching about any matter that attacks their attention in an autonomous way and according to their own interests. Finally, the elaboration of this project beneficiated students that were carrying out their research projects because they were allowed to consult a physical catalogue where the bibliographical material is organized according to the research lines of our program, so they could find tentative material to support their studies.